Surface engineering of silica nanoparticles with a gadolinium–PCTA complex for efficient T1-weighted MRI contrast agents. (14th October 2020) - Mathieu, Paul; Chalet, Marie; Clain, Marie Myriam; Teulon, Lauryanne; Benoist, Eric; Leygue, Nadine; Picard, Claude; Boutry, Sébastien; Laurent, Sophie; Stanicki, Dimitri; Hénoumont, Céline; Novio, Fernando; et al.
Abstract : Covalent grafting of diaqua Gd(iii )-complexes onto dense silica nanoparticles affords non-toxic contrast agents suitable for high field MRI pre-clinical studies. Abstract : New pyridine containing triAza; 3, 6, 9, 15-tetraazabicyclo[9.3.1]pentadeca-1(15), 11, 13-triene-3, 6, 9-triacetic acid (PCTA) ligands presenting pendant carboxylic acid or alcohol functions have been synthesized and used to form diaqua Gd(iii ) complexes, which have been immobilized onto dense silica nanoparticles. Cytotoxicity studies of these complexes (free or immobilized on the nanoparticles) on normal 1BR3G cells and cancerous HCT 116 cells indicated a dependence on the pendant chemical group for the free complexes. However, this effect disappeared once the complexes were immobilized on the surface of the nanoparticles, leading to non-toxic nanomaterials. The interest of these complexes (free or immobilized on dense silica nanoparticles) as contrast agents in magnetic resonance imaging (MRI) has been evaluated in comparison with DOTAREM® by recording their nuclear magnetic resonance dispersion (NMRD) profiles, measuring their transversal and longitudinal relaxivities as well as recording images on phantoms at 37 °C. This study has evidenced the high potential of these complexes: first it suggested the possibility to reduce the dose to be injected by a factor of 10, second it evidenced their high efficiency in high field T 1 -weighted MRI (9.4 T), the key towards images of higher resolution and shorter acquisition times.